Whose Century? Narrative Power in Streaming Alternate-History Television. Issue 4 (2nd October 2022) - Osur, Summit P.
Abstract: Although alternate histories have been present since the early days of televised science fiction, the genre didn't take off until the streaming era of television began. Direct-targeted advertising, a glut of content, the maturation of the genre, and the historical instability of the twenty-first century intersected in the alternate-history genre, making it not only an important artistic genre but an important political one as well. Traditionally, the alternate-history genre, on a whole, has been criticized for its closed narratives that support the Great Man theory of history through an overemphasis on battles and royalty. A case study of six recent televised alternate histories— Russian Doll, Undone, Bandersnatch, Loki, Watchmen, and For All Mankind —shows that the televised version of the genre has matured into a revisionist genre that is focused on the natural determinism and personal agency as well as on the social factors that impact both. Taken together, these six shows suggest a unique maturity in the alternate-history genre, one that questions Anglo-Saxon spheres of narratological power and the very linearity of Western history.